PATH-42. EGFR-AMPLIFIED IDH-WILDTYPE GLIOBLASTOMAS SELDOM TRANSFORM INTO A HYPERMUTATED PHENOTYPE. (5th November 2018) - Draaisma, Kaspar; Chatzipli, Aikaterini; Taphoorn, Martin; Kerkhof, Melissa; Weyerbrock, Astrid; Sanson, Marc; Hoeben, Ann; Lukacova, Slavka; Lombardi, Giuseppe; Hanse, Monique; Fleisscheuer, Ruth; Leenstra, Sieger; et al.
Abstract: INTRODUCTION: Current efforts to improve patient survival in recurrent glioblastomas (GBMs) are often based on targeting the tumors acquired genetic changes. However, most molecular data is derived from the initial tumor: resections of recurrent GBMs are seldom performed. This study aims to assess whether genetic traits of initial GBMs are still present at recurrence. METHODS: DNA/RNA was isolated from pairs of initial and recurrent Stupp-treated GBM tumor samples (FFPE) and sequenced on a panel of 365 cancer genes. MGMT promotor methylation was determined by MS-PCR, EGFRvIII by RT-PCR and TERT-promotor mutations by SNaPshot. RESULTS: 276 patients from ten medical centers in six countries were identified with median age of 54.1 years. Median survival was 23.7 months, and median time to second surgery 13.0 months. Only 10 of 186 sequenced matched tumor pairs were IDH-mutated (5.4%). Overall, genetic traits of initial GBMs were stable with a median retention rate of coding mutations of 81.8%. Similarly, copy number changes (CNVkit/GISTIC) generally were retained at tumor recurrence. However, the retention rate was also ~80% in all of the major GBM driver pathways (TP53 signaling, RAS-RAF-MEK-ERK, RTK signaling). This is important as decreases 20% of loss of a marker requires a doubling of the number of included patients to achieve a similar power (assuming an objective response rate of 40% as a positive outcome). One noticeable change was a loss of TERT-promoter mutations in 7.5% of recurrent samples. Only four tumors were hypermutated (> 100 coding mutations) at recurrence, though more samples (n=12) acquired mutations in MSH2 and MSH6. Only one EGFR-amplified tumor was hypermutated. CONCLUSION: EGFR-amplified GBMs seldom transform into hypermutated tumors which suggests immune-checkpoint inhibitors have limited clinical use in recurrent GBMs. Re-sampling should be considered prior to inclusion in targeted therapy trials to ensure proper patient selection.